The Influence of Product Knowledge, Brand Image, and Brand Love on Purchase Decision through Word of Mouth - Ayuningsih, Fitria; Maftukhah, Ida (Universitas Negeri Semarang, 2020)
This study aims to determine the direct and indirect effects of product knowledge, brand image, brand love, and word of mouth as intervening variables on purchase decisions. The population in this study were all JimsHoney bag consumers in Semarang. Sampling was carried out using the purposive sampling technique, the number of samples was 116 respondents. The data collection method used a questionnaire and documentation. Methods of data analysis using classic assumption tests and hypothesis testing with the IBM SPSS Statistics 25 program. The results of this study indicate that product knowledge and brand love have a positive effect on purchase decisions. The brand image does not effect on purchase decisions. As well as product knowledge, brand image, and brand love have a positive effect on purchase decisions through word of mouth. Word of mouth has an important role in influencing purchase decisions. Therefore, companies must be able to create and maintain good word of mouth among consumers to attract attention and win consumers' hearts.